Review on Phytochemical and Pharmacological Aspects of Dolichos biflorus Linn - Gupta, S.K.; Sharma, P.K. (Asian Journal of Chemistry, 2016)
Dolichos biflorus Linn. (Leguminosae) is an important medicinal plant, which finds uses in Ayurveda and Unani systems of medicine especially for removing kidney stones. It has diuretic and emmenagogue effects. An attempt has been made to review the phytochemical, pharmacological and antimicrobial works done on this plant.